A Playful Approach to Household Sustainability: Results From a Pilot Study on Resource Consumption. (February 2023) - Agusdinata, Datu Buyung; Lukosch, Heide; Hanif, Muhammad; Watkins, David
Background: U.S. households produce a significant amount of greenhouse gas emissions, indicating a potential to reduce their carbon footprints from changing food, energy, and water (FEW) consumption patterns. Behavioral change to FEW consumption is needed, but difficult to achieve. Interactive and engaging approaches like serious games could be a way to increase awareness of possible measures, leading to more sustainable behavior at a household level. This study looks into the experiences and effects of a digital game for homeowners with the potential to reduce FEW resource consumption impacts. Intervention: In this study, we developed and implemented a digital game to explore its potential to raise awareness of the consumption and conservation of FEW resources and the efficacy of conservation messages. This study aims to measure learning outcomes from game participation and to assess the suitability of the game for informing resource conservation actions. Methods: We tested a proof-of-concept of a digital four-player game, called HomeRUN, with 28 homeowners. The data collected include homeowners' values and preferences with regard to FEW resources. The patterns of game actions are analyzed with an emphasis on the effectiveness of conservation messaging in informing household consumption behavior. Results: About 65% of the respondents agree that they gained a better understanding of the greenhouse gas emission impacts of FEW resource consumption after playing the game. Over 57% of the respondents agree that the game experience would influence their future consumption behavior, while a quarter of the respondents are unsure. Overall, we demonstrate the HomeRUN game has potential as a tool for informing conservation efforts at a household level.